Sumbangan Pengajian Ilmu Qiraat di Era Moden: The Contribution of Qirāʾat Studies in the Modern Era - Gumaa Ahmed Himmad; Ahmad Baha’ bin Mokhtar; Rifqi Hidayatil (Maʿālim al-Qurʾān wa al-Sunnah, 2023)
This article aims to reveal the contribution and importance of the study of Qirāʾat science in the modern era. Muslim scholars have emphasised it since immemorial times, even before several other sciences were discussed. This article conducts qualitative research and will reveal several reasons why the science of Qirāʾat needs to continue to be maintained. Although the description does not cover all aspects, it is hoped that it can represent and illustrate the purpose of this article. The research results found that the study of Qirāʾat science is a form of preserving the special qualities of al-Quran al-Karim. It is a reference and source that has an important role in Islamic studies such as tafsir, fiqh, and language. Apart from that, it can also oppose every challenge and accusation made by the enemies of Islam that aim to undermine the honour and dignity of the Qur'an. So, the study of the science of Qirāʾat in the modern era is an important thing that must be continued, because the extinction of the science of Qirāʾat will result in the burial of some of the words of Allah S.W.T. and the disappearance of the treasures of knowledge. It could even be the loss of a way of life for Muslims.